The Effect of Organizational Justice on Organizational Commitment and Organizational Citizenship Behavior (OCB) with Job Satisfaction as Mediation - Cyntia Puspita; Meiske Claudia (Cita Konsultindo Research Center, 2024)
This research aims to determine and analyze the effect of Organizational Justice (X) as an independent variable on Organizational Commitment (Y1) and Organizational Citizenship Behavior (OCB) (Y2) as a dependent variable and to analyze Job Satisfaction (Z) mediating Organizational Justice towards Organizational Commitment and Job Satisfaction (Z) mediating Organizational Justice towards Organizational Citizenship Behavior (OCB) in civil servants employees at the Kapuas Regency Trade, Industry, Cooperatives and Small and Medium Enterprises Service Office. This research method used a questionnaire with 28 civil servants employees from the Kapuas Regency Trade, Industry, Cooperatives and Small and Medium Enterprises Service Office as samples. Variable measurement used the Likert Scale technique with a weight scale of 1 to 7 and to test the level of significance using path coefficient analysis processed with the SmartPLS 4.0 program. The research results concluded that Organizational Justice influences Organizational Commitment. Organizational Justice influences Organizational Citizenship Behavior (OCB). Organizational Justice influences Job Satisfaction. Job Satisfaction has no effect on Organizational Commitment. Job Satisfaction has no effect on Organizational Citizenship Behavior (OCB). Job Satisfaction does not mediate the effect of organizational justice on Organizational Commitment. Job Satisfaction does not mediate the effect of organizational justice on Organizational Citizenship Behavior (OCB).